A Carta Guarani Kaiowá e o direito a uma literatura com terra e das gentes - Marília Librandi-Rocha (Estudos de Literatura Brasileira Contemporânea)
This article proposes to consider the Guarani Kaiowa ’ s Letter as part of contemporary Literature produced in Brazil. This inclusion presents itself as a theoretical challenge because it obligates us to explicit what we understand by “literature”, its connections to Human Rights, and which place this letter occupies within the history of Brazilian literature. The final aim is to think not only about “o ur” literature, historically linked to the colonial and then to the national system, but about a post - colonial literature produced and signed by the pluralities of people living in Brazil.